An investigation of a heat pump system using CO2/propane mixture as a working fluid. Issue 1 (2nd January 2017) - Zhang, Xianping; Wang, Fang; Fan, Xiaowei; Duan, Huanlin; Zhu, Feiyu
ABSTRACT: In order to decrease the heat rejection pressure of heat pump using pure working fluid, CO2 or R744, other natural component including hydrocarbons (R290, R600a, R600, R1270, R170, R601) and dimethyl ether (RE170) is added to CO2, respectively, and then six binary mixtures are achieved. By environmental and thermodynamic comparisons, R290 is selected to be the most appropriate component candidate to mix with CO2, and meanwhile to weaken the flammability and explosivity for pure R290. Then, the system performances of heat pump using mixture of CO2 and R290 were experimentally studied when R290 is added to CO2 with a small fraction, and compared with that of the pure CO2 . The experimental test rig is designed and set up for the transcritical heat pump system. When the refrigerant charge is variable, the heating coefficient performance, optimum heat rejection pressure, compressor power, mass flow rate of refrigerant, and total heat coefficient of gas cooler were researched. The variation ratios of heating coefficient performance and heating capacity with deviation from the optimum refrigerant charge were also investigated. The optimum refrigerant charge of CO2 /R290 is obtained and the research results show that the addition of R290 to CO2 can efficiently reduce the heat rejection pressure and improve the system performance. The results in the present work could provide useful guidelines for the design and operation of heat pump system using CO2 -based mixture.